DNA ligase IV dificiency with elevated serum IgG levels suspected to have myelodysplastic syndrome: a case report - Miao Huang; Guoqing Dong; Xiyan Lu; Fei Xiao; Qixin Zhou; Shaoyi Zhang (BMC Pediatrics, 2022)
Abstract Background Ligase IV (LIG4) dificiency is a very rare clinical syndrome with around 50 cases reported to date. This syndrome is caused by biallelic pathogenic variants in the LIG4 gene, which cause DNA damage repair disorders, mainly manifesting as severe immunodeficiency. Case presentation We report the case of a 15-month-old male child with pancytopenia, growth retardation, microcephaly, history of vaccine-related rubella, elevated immunoglobulin G, and decreased T- and B lymphocytes. Next-generation sequencing revealed LIG4 pathogenic genes and compound heterozygous mutations, namely the missense mutation c.833G > T (p.Arg278Leu) and deletion mutation c.1271_1275del (p.Lys424Argfs*20). Conclusion This case suggests that LIG4 dificiency can manifest not only as immunodeficiency but also with increased serum IgG levels and pancytopenia, which constitutes an additional clinical phenotype. Furthermore, this case suggests that LIG4 deficiency should be considered upon differential diagnosis of myelodysplastic syndrome in children.